Strategies of English Literature Teaching at English Literature Undergraduate Program at Sunan Gunung Djati State Islamic University - Udayani Permanaludin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2017)
This research is originated in a wide gap between literature knowledge and didactic-methodical realm for those literary lectures at the research site. In fact, the method of English literary teaching is contextually considered being urgent to implement in the world of literary education. The teaching of English literature, so far, is under the shadows of English teaching since it becomes a global language. Hence, the teaching of English litearture has a broad domain to research. As a trend lasting in the global education in modern age, it is necessary to learn and research strategies of English literary teaching practiced within the classrooms.Such a research used a descriptive-qualitative method. The research data were collected through three techniques: observation, interview, and documents. The results of the three techniques are triangulated to be an intact information on the literary teaching, so-called primary data. The data analysis techniques used in this research, later on, are data identification, data categorization, data analysis and interpretation, and conclusion. The result shows that seven respondents (lecturers) still used expocitory approach with the formal methods (lecturing, question-answer, group discussion) in their English literary teaching. They have not applied explorative method in which learning-based approach focuses on the students in the literary teaching. However, there are six difficulties (problem) in the teaching of English literature and thirteen solution to overcome those ptoblems based on the observation and interview data.